A review of biometric template protection techniques for online handwritten signature application - Layth Malallah F.; Sharifah Mumtazah Syed A.; Yussof S.; Wan Adnan W.A.; Iranmanesh V.; Arigbabu O.A. (2023)
Handwritten signature biometric is considered as a noninvasive and nonintrusive process by the majority of the users. Furthermore, it has a high legal value for document authentication, as well as being dependent on by both commercial transactions and governmental institutions. Signature verification requires storing templates in the database, which threatens the security of the system from being stolen, to being vulnerable to the template playback attack that may give an attacker an invalid access to the system. Moreover, an individual cannot use his / her signature with two applications or more, otherwise, a cross matching problem will occur. The aforementioned problems can be avoided by using biometric template protection techniques for the online signature, which have been reviewed and discussed in this paper considering both protections and verification. Furthermore, the verification elaboration comprises of capture devices, pre-processing, feature extraction and classification methods. 2013 Praise Worthy Prize S.r.l. - All rights reserved.